Comparison of survival outcome of patients with primary peritoneal and fallopian tube carcinoma treated with neoadjuvant chemotherapy versus primary debulking surgery. (2nd January 2017) - Soleymani majd, Hooman; Ismail, Lamiese; Hardern, Kieran; Ferrari, Federico; Kehoe, Sean
Abstract: This study examines the overall survival of primary peritoneal cancer (PPC), in those patients who had primary debulking surgery (PDS) followed by six cycles of chemotherapy versus those who had neoadjuvant chemotherapy (NACT). This was a prospective observational study performed at Oxford Gynaecological Cancer Centre, over a 5-year period. Eighty-seven patients were clinically suspected of having PPC. Histology confirmed that 64 of these were PPC, with the balance being tubal in origin. PDS was performed in 31 cases. Although NACT was planned in 56 patients, 4 patients didn't receive NACT and therefore excluded from the survival analysis. The overall median survival was 34 months. However, the 5-year survival was 12%. Survival in the PDS group was 46 months versus 24 months in the NACT ( p  = .011). The conclusion drawn from this study is that patients affected by PPC, selected for PDS have a greater survival advantage than those who had NACT.